Risk factors for unplanned readmissions in paediatric neurosurgery: a systematic review - Lance Vincent Caburian Sese; Ma Celina Legaspi Guillermo (BMJ Open)
Objectives Unplanned hospital readmission (UHR) after paediatric neurosurgery is an important indicator of surgical outcomes. As this field deals with complex cases, there is an increased likelihood of potential complications and the subsequent need for readmission. We estimated paediatric neurosurgery UHR rates globally and identified significant factors contributing to 30-day and 90-day UHR rates in children undergoing neurosurgical procedures.Design A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources Embase, Medline, CINAHL and Global Index Medicus databases were searched on 17th December 2023.Eligibility criteria We included studies that reported unplanned readmissions in the paediatric population within 30 days and 90 days of an index neurosurgical procedure.Data extraction and synthesis Two independent qualified researchers screened studies and extracted data using standardised methods. Risk of bias assessment was done using the Newcastle-Ottawa scale. Narrative synthesis was performed.Results 2593 titles were identified following the search strategy. 52 studies were included after screening, full-text review and quality appraisal. Most studies were from the USA and are retrospective cohorts. The majority were cranial procedures (n=30), with common ones being shunt procedures for hydrocephalus and cranial tumour resections. 30-day readmissions ranged from 1.4% to 28% while 90-day readmissions ranged from 1.31% to 38.64%. 34 different risk factors were identified. Aetiology-related factors, procedure-specific complexities and age emerged as the three most common. Other common risk factors were complex chronic conditions, race, length of hospital stay and type of medical insurance. The patient’s age was a significant non-modifiable predictor, with younger children generally facing higher odds compared with their older counterparts across different procedures. While early readmissions could be due to disease progression, some were linked to preventable causes. Heterogeneity was also present due to variations in definitions and inclusion of studies from both national databases and single institutions.Conclusions Findings from this study contribute to a collective understanding of factors affecting unplanned readmissions in paediatric neurosurgery. UHRs reflect the interplay among surgical complexity, patient characteristics such as age and disease aetiology.